Isolation and preliminary characterization of erythromycin-resistant variants of Legionella micdadei and Legionella pneumophila. - Dowling, J N (1985)
Erythromycin-resistant Legionella spp. variants were obtained by a single passage of the naturally occurring bacteria on medium containing various concentrations of erythromycin. By disk diffusion susceptibility testing, at least three different phenotypic patterns of cross-resistance to macrolide, lincosamide, and streptogramin B antibiotics were observed among the 26 erythromycin-resistant strains examined.